Experimental and Numerical Study on Single-Bolted Cold-Formed Angles under Tension and Compression - Fasoulakis, Zacharias C.; Raftoyiannis, Ioannis G.; Avraam, Tassos P. (Frontiers in Built Environment, 2017)
Angle sections are commonly designed to bear only axial force, usually neglecting the additional bending moments resulting from the eccentric connection and the shift of the effective centroid. The current work deals with the capacity of single-bolted equal angle sections made from cold-formed steel. The experimental investigation presented herein includes tension and compression tests which subsequently are compared with the corresponding code provisions. Numerical analyses are also presented based on a detailed finite element simulation. Finally, a reliability analysis is implemented in order to demonstrate the reliability of the design rules for cold-formed steel angle columns. Results indicate a small discrepancy on the strength prediction in general by EN 1993-1-3, as well as by the AISI for slender columns and a more conservative one by EN 1993-1-1. A comparison of the above results is clearly illustrated herein in graphical forms.